Supplementation of Chlorogenic Acid Alleviates the Effects of H2O2-Induced Oxidative Stress on Laying Performance, Egg Quality, Antioxidant Capacity, Hepatic Inflammation, Mitochondrial Dysfunction, and Lipid Accumulation in Laying Hens - Haitong Zhao; Zhuang Li; Yue Sun; Ming Yan; Yingjie Wang; Yurong Li; Yeshun Zhang; Mingkun Zhu (Antioxidants)
This research examined the impact of chlorogenic acid (CGA) on laying performance, antioxidant capacity, egg quality, hepatic inflammation, mitochondrial function, and lipid metabolism in hens subjected to hydrogen peroxide (H2O2)-induced oxidative stress (OS). Three hundred sixty healthy 43-wk-old Hy-Line brown hens were randomly assigned to six treatments: a basal diet + 0 (control and H2O2), 600 (600 mg/kg CGA and 600 mg/kg CGA + H2O2), and 800 (800 mg/kg CGA and 800 mg/kg CGA + H2O2) mg/kg CGA for 84 d. On the 64th and 78th days of the trial, hens in groups H2O2, 600 mg/kg CGA + H2O2, and 800 mg/kg CGA + H2O2 were injected intraperitoneally with 10% H2O2. The results demonstrated that 600 and 800 mg/kg CGA significantly improved the egg production rate (EPR) and egg quality and reduced lipid peroxidation compared to the control group. The 800 mg/kg CGA showed greater improvements in the EPR and average egg weight (AEW) compared to the 600 mg/kg dose. Conversely, H2O2 exposure significantly decreased the EPR, AEW, and egg quality and increased feed conversion rate and average daily feed intake. H2O2 exposure significantly decreased serum T-AOC and increased serum MDA levels while reducing hepatic T-SOD, GSH-Px, and CAT activities. Meanwhile, H2O2 exposure significantly elevated liver reactive oxygen species levels, pathological damage, and NF-κB, TNFα, and IL-1β gene expression. Additionally, H2O2 treatment disrupted hepatocyte mitochondrial structure and significantly increased the expression of VDAC1 protein, and IP3R, GRP75, MCU, Fis1, and MFF genes, while downregulating the expression of MFN2 protein and PGC1α gene. Oil Red O staining demonstrated that H2O2 induced significant lipid accumulation in hepatocytes. Concurrently, H2O2 significantly increased serum triglycerides, total cholesterol, and liver triglycerides levels while decreasing serum hepatic lipase activity. This was primarily attributed to the significant upregulation of liver SREBP1, FASN, and ACC genes and the downregulation of the liver CPT1 gene induced by H2O2. Furthermore, CGA pretreatment effectively prevented the degeneration in laying performance and egg quality, as well as OS, liver inflammation, pathological damage, and mitochondrial dysfunction induced by H2O2. CGA inhibited H2O2-induced hepatic lipid accumulation by upregulating fatty acid oxidation-related gene expression and downregulating fatty acid synthesis-related gene expression. These findings indicate that the dietary addition of 800 mg/kg of CGA is the optimum supplementation dose. CGA can enhance laying performance and egg quality while alleviating OS, hepatic inflammation, mitochondrial dysfunction, and lipid accumulation in H2O2-challenged laying hens.